The Effect of Classroom Management on Pupils’ Motivation to Learn - Rahma Dina Asrina; Lili Nur Indah Sari; Ade Suhendra (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2026)
This study aims to analyse the effect of classroom management on students’ motivation to learn in the Akidah Akhlak subject for Year 10 pupils at MAN 1 Padangsidimpuan. This study employed a quantitative approach using a survey method. The results indicate that classroom management has a positive and significant effect on students’ learning motivation. The results of the simple linear regression test showed a regression coefficient of 0.686 with a significance level of 0.000 (